Entropia de Volume ao Longo de Fluxos do Tipo Yamabe - Wilfredo Renato Lavado Enco (2017)
In this work we study the existence and smooth convergence of Yamabe-type flows solutions on Riemannian and Finsler manifolds. Under the assumption of the existence of a metric g with negative curvature, we demonstrate that it is controlled by a Yamabe metric which is in the same equivalence class of g. In particular, we demonstrate that the volume entropy of the original metric is controlled by the volume entropy of the Yamabe metrics.